Three new species of subgenus Distephana (Juss) Kilipp (Passifloraceae) for Rondonia, Brasil Species of Subgenus Distephana Rondônia (Revista de Investigaciones Universidad del Quindío, 2010)
We are describing three new species of subgenus Distephana (genus Passiflora) to Rondônia State, in the Brazilian Amazonia: Passiflora glandulosa Cav, P. tholozanii Sacco and P. vitifolia Kunth. In addition to the early described, P. coccinea Ambl., P. araujoi Sacco and P. variolata Poep & Endl., presence of these new species points to the diversity of the subgenus in this region, which is represented by alow number of species through Brasil.
Keywords: género Passiflora; Amazonia brasileña; subgénero Distephana; supersección Distephana